Reducing Energy and Water Consumption in Textile Dyeing Industry with Cleaner Production by Inlet-Outlet Modification to Reuse Wastewater: Reducing Energy and Water Consumption in Textile Dyeing Industry - Yandri, Erkata; Idroes, Rinaldi; Setyobudi, Roy Hendroko; Rudationo, Carolus Boromeus; Wahono, Satriyo Krido; Mahaswa, Rangga Kala; Burlakovs, Juris; Susanto, Herry (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Dyeing Finishing (DF) textile industries which consume a lot of energy, chemicals, water, etc., then produce a lot of wastewater which creates significant environmental problems, can be anticipated by applying Cleaner Production. This paper is presented to discuss the technical modification process of dyeing production machines, which reuse process wastewater to save water and energy consumption in the production process. For that reason, there are three steps taken. First, understand the process flow of the textile dyeing industry. Second, understand in detail the dyeing process of the Jet Dyeing (JD) machine. Third, implement steps on the floor, focusing on the JD machine, starting from the initial conditions until the third step. As a result, savings in water consumption per day for 10 JD machines were achieved by almost 50 %, with details; at the initial status 700 000 L, 600 000 L in the first step, 430 000 L in the second step, and finally 400 000 L in the third step. A similar action can be carried out in other processes, such as washing, de-sizing, or in other industries which also consume a lot of water and energy.